Modified model of equivalent height for predicting atmospheric attenuation at frequencies below 350 GHz. Issue 8 (4th April 2018) - Li, Haiying; Wu, Zhensen; Zhao, Zhenwei; Lin, Leke; Lu, Changsheng; Qu, Tan
Abstract : Due to atmospheric absorption, the signal attenuation must be considered when designing communication links in the terahertz (THz) band. The equivalent height described in International Telecommunication Union Recommendation (Rec. ITU)‐R P.676 can be used to evaluate the signal attenuation over satellite links by meteorological parameters of the Earth's surface, which are relatively convenient to obtain. Since both temperature and water vapour content can greatly influence the absorption of THz waves and have temporal and spatial variability, the equivalent height should be a combined value representing the influences of temperature, water vapour, and pressure. However, only pressure is considered in the ITU‐R P.676 model. As a result, it will cause inaccuracies for different regions and seasons. In this study, a modified model of the equivalent height with temperature and water vapour near the Earth's surface is proposed. Compared with the forward equivalent heights, the equivalent heights based on both models are evaluated. Analyses of the window frequencies are performed, and improved results are achieved with the modified model, especially for mid‐ and high‐latitude winter profiles. The accuracy of the modified model for other profiles is also analysed and the results indicate its suitability.